Phenotypic Variability of Ceratocystis paradoxa Isolated from North Western and Western Provinces of Sri Lanka and its Bio Control by Potential Bio-Control Agent; Trichoderma viride - Jayaratne, D. L.; Dayarathna, M. T. A. (International Coconut Community Journal, 2015)
Coconut (Cocos nucifera) is an important economic crop in Sri Lanka; one of the world's largest exporters of coir fiber and coir products. Ceratocystis paradoxa is a pathogen causing stem bleeding, leaf and fruit rot in variety of crop plants including coconut. Since C. paradoxa is associated with coconut trees, there is an opportunity for the pathogen exist in coir and coir products as well. According to the quarantine requirements, this pathogen has to be free in coir and coir products that are exported from Sri Lanka. During this study the pathogen was isolated from the samples of coir collected from different locations in North Western Province and Western Province of Sri Lanka. Colony morphology and spore morphology were compared among these isolates. Bio-control and the sensitivity of the isolates to the antagonist were evaluated against Trichoderma viride. According to the results the pathogen was present in all the samples collected from different locations of the coconut growing triangle. The isolated colonies grown on Potato Dextrose Agar (PDA) plates were white in early stage but became black, one or two days later. The growing colonies produced two asexual spores; the endoconidia and chlamydospores. Endoconidia are formed in the conidiophores making long chains. They are thin-walled cylindrical 9-12 µm x 4.8-7.2 µm in size, yet two isolated from North Western Province had a smaller width of 2.4 µm endoconidia. Chlamydospores are thick walled formed in short chains, dark color, and are mostly oval shaped, 9.6-16.8µm x 7.2-9.6µm in size, yet one isolated from North Western Province had a width of 4.8 µm. The chlamydospores are varied in morphology according to the geographical distribution of the pathogen. The variability of chlamydospore morphology predicts the genomic variability among the isolates. Biological control of C. paradoxa using T. viride was successful in all the isolates used in vitro studies. The experiments showed similar effects of T. viride on all C. paradoxa isolates as the biological control agent by killing the vegetative growth and losing the spore viability.